Från flygkamrater till rymdrevolutionärer. Om Sven Wernströms tidigaste science fiction - Jerry Määttä (Barnboken: Tidskrift för Barnlitteraturforskning, 2012)
The Swedish author Sven Wernström (b. 1925), mostly known for his political children’s and young adult fiction, is also one of the most prolific and widely read Swedish writers of science fiction (sf). His first attempts in the genre consisted of stray sf elements in some of his aviation novels on ‘‘Flygkamraterna’’ (‘‘The Flight Comrades’’, 1947-1957), and the fullblown sf novel Flygkamraterna korsar rymden (‘‘The Flight Comrades Cross Space’’, 1949), which depicts a trip to Mars and an encounter with an alien civilisation literally divided into different strata in their underground society. This study examines the transition from Wernström’s first aviation novels to his first sf novel, and studies the extent to which Wernström’s early science fiction makes use of the specific conventions of the genre. After a very brief survey of the history of sf in Sweden up until the 1950s, this study deals with the two novels Flygkamraterna (‘‘The Flight Comrades’’, 1947) and Flygkamraterna korsar rymden  when it comes to their view on science and technology, their uses of technological speculation and futurological extrapolation, estrangement, and evocation of the sublime. It is commonly believed that Wernström’s writing didn’t really become political until the 1960s. One of the main conclusions of this study, however, is that already in his earliest science fiction from the late 1940s, Wernström makes ample use of the genre’s potential to conduct indirect social commentary. Keywords: Sven Wernström; Science Fiction; Aviation Novels; Interplanetary Travel; Mars; Alien Life Forms